Socio-ecological sustainability and school garden in the early years of elementary school: a systematic literature review - Valdenildo Pedro da Silva; Francidalva Vieira Alves de Assis (Journal of Science and Education (JSE), 2021)
Other transgressive learning about sustainability needs to be part of the lives of students in the early years of elementary school, as they are responsible for seeking and achieving a sustainable future. However, the focus on socio-ecological sustainability does not seem to be present at this level of education as the literature has addressed. Therefore, the objective is to review articles from journals that address the relationships on socio-ecological sustainability and school garden in the early years of elementary school, published from 2016 to 2021. Based on the ideas of Okoli and Schabram (2010), they used if, in the research, the SciELO and Google Scholar databases and 10 papers were chosen, which were read in full for analysis and discussion. The results show a limited focus on how the teaching of socio-ecological sustainability and school garden has been carried out in elementary school, that is, interdisciplinarity is not widespread and the approach to this sustainability, through the use of the school garden, is non-existent in classroom. It was noticed in the articles that the school garden is insufficiently used in teaching, despite its relevance in teaching-learning, as well as the sustainability addressed in schools involves only the economic dimension when it is essential to connect the social and ecological approach.